Structural colour from helicoidal cell-wall architecture in fruits of Margaritaria nobilis - Vignolini, Silvia (J R Soc Interface, 2016)
The bright and intense blue-green coloration of the fruits of Margaritaria nobilis (Phyllanthaceae) was investigated using polarization-resolved spectroscopy and transmission electron microscopy. Optical measurements of freshly collected fruits revealed a strong circularly polarized reflection of the fruit that originates from a cellulose helicoidal cell wall structure in the pericarp cells. Hyperspectral microscopy was used to capture the iridescent effect at the single-cell level.